PENERAPAN MEDIA VIDEO EDUKASI TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN SIRAH KELAS 5C SALAFIYAH ULA ICBB YOGYAKARTA - Anggi, Anggi; Karimah, Karimah; Wardani, Widyaningtyas Kusuma (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The advancement of digital technology has significantly transformed the learning process in elementary schools, including the teaching of Sirah, which has traditionally relied on conventional methods. This study aims to describe the use of educational video media and analyze its impact on students’ learning motivation in class VC at Salafiyah Ula ICBB Yogyakarta. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data reduction, presentation, and conclusion drawing. The findings reveal that the use of educational video media creates a more engaging, dynamic, and enjoyable learning atmosphere. Videos depicting the struggles of the Prophet and his companions visually captured students’ attention, stimulated curiosity, and enhanced their emotional engagement with the learning material. Moreover, video media helped improve students’ self-confidence, encouraged collaboration during group discussions, and fostered a more enthusiastic and reflective learning attitude. Overall, the integration of educational videos has a significant positive effect on students’ motivation and participation in learning Sirah.